2021
DOI: 10.1111/1755-0998.13501
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐level genome of Antechinus flavipes provides a reference for an Australian marsupial genus with male death after mating

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 133 publications
3
17
0
Order By: Relevance
“…Interspersed repeats constituted ~56% of the assembly (Supplementary Table 5). Consistent with the highly conserved genome organization of dasyuromorphs, the thylacine had similar overall repeat composition to its living relatives (Tian, et al 2022). The dominant repeat class was LINE elements (~36.5%), occurring at a frequency comparable to that of the Tasmanian devil (~39%), though somewhat lower than that of the brown antechinus (~45%) (Tian, et al 2022).…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Interspersed repeats constituted ~56% of the assembly (Supplementary Table 5). Consistent with the highly conserved genome organization of dasyuromorphs, the thylacine had similar overall repeat composition to its living relatives (Tian, et al 2022). The dominant repeat class was LINE elements (~36.5%), occurring at a frequency comparable to that of the Tasmanian devil (~39%), though somewhat lower than that of the brown antechinus (~45%) (Tian, et al 2022).…”
Section: Resultssupporting
confidence: 64%
“…Consistent with the highly conserved genome organization of dasyuromorphs, the thylacine had similar overall repeat composition to its living relatives (Tian, et al 2022). The dominant repeat class was LINE elements (~36.5%), occurring at a frequency comparable to that of the Tasmanian devil (~39%), though somewhat lower than that of the brown antechinus (~45%) (Tian, et al 2022). Interestingly, we observed that LTRs were sparse in the thylacine genome (~1.51%) compared to previously studied marsupial species (which ranged from 6.53%-18.89%; Supplementary Table 5) (Tian, et al 2022).…”
Section: Repeat Classification and Genome Annotationsupporting
confidence: 60%
See 2 more Smart Citations
“…Similar phenomenon has been observed in mammals. Male pouched mice ( Antechinus ) experience severe hormonal disbalance during the mating period that results in their death at the end of mating period [ 73 ].…”
Section: Altruismmentioning
confidence: 99%